Documentary storytelling : creative nonfiction on screen - Bernard, Sheila Curran. 4 0 16; 5 (Amsterdam : Elsevier/Focal Press, 2011)
A practical guide to documentary filmmaking that examines the story and structure of documentaries and offers filmmakers practical tips and expert advice for every stage of the process.
Includes bibliographical references (p. [347]-352), filmography (p. [353]-359), and index.
Keywords: 2 -- 0; 6; Production and direction.;Authorship. -- Documentary films;Documentary films -- 20; 20; 2